322. Evaluation of the performance parameters on the Ingenuity TF PET/CT scanner. (December 2018) - Sutov, D.; Zorz, A.; Rossato, M.; Zandonà, R.; Branchini, M.; De Monte, F.; Pena, L.M. Arana; Riccardi, L.; Paiusco, M.
Abstract : Purpose: To evaluate the performance characteristic of Philips Ingenuity TF PET/CT system with the new Pixelar detector design. A comparison of different image reconstruction protocols for EARL accreditation programme was performed. Methods: Performance measurements on PET scanner were performed according to the NEMA NU2-2012 standard. Image quality was extended by accounting for different reconstruction parameters (frame timing, PSF iteration number, PSF regularization). A NEMA Image quality phantom was used for suitable image reconstruction protocol evaluation, according to EARL guideline. Performance measurements on CT scanner were performed according to IAEA No.19 publication. Geometrical efficiency was evaluated by exposure of various beam collimations on radiochromic films. Image quality parameters (MTF, Noise) using all reconstruction filters and iterative reconstruction (IDose) were obtained by Catphan®600 acquisitions. Influence of current modulation on patient dose (DoseRight) was studied using an anthropomorphic phantom. Results: Spatial resolutions ranged from 4.6 mm at 1 cm to 6.0 mm at 20 cm. Sensitivity measured in the centre and at 10 cm were 7.58 and 7.43 cps/kBq, respectively. The measured NECR peak was 122.7 kcps at 20.3 kBq/cm3. The scatter fraction was 36.6%. Results of image quality test are reported in table. Manufacturer's EARL dedicated reconstruction protocol did not perfectly meet accreditation requirements as others reconstructions with PSF. CT acceptance parameters met manufacturers and international guidelines specifications, except from geometrical efficiencies for 5 mm, 2.5 mm and 1 mm beam collimations. Decreasing DoseRight index from 26 to 24 and 16, dose reductions of 19.8% and 67.3% were observed. Conclusions: Philips Ingenuity TF PET/CT system has overall good performance characteristics, comparable with similar scanners from other manufacturers. The CT part performance meets manufacturer's specifications with some discrepancies, which do not have a significant impact on clinical use. Regarding EARL accreditation programme, a better adjustment of reconstruction protocol is needed.